PRODUKSI BIOETANOL SECARA SHF DAN SSF MENGGUNAKAN Aspergillus niger, Trichoderma viride DAN New Aule Instant Dry Yeast PADA MEDIA KULIT UBI KAYU - Jay Jayus; Sony Suwasono; Ike Wijayanti (Faculty of Agricultural Technology, University of Jember, 2017)
Effort to improve the yield of bioetanol production from cassava peels were be carried out by separated hydrolysis fermentation (SHF) and simultaneous saccharification fermentation (SSF) using Aspergillus niger, Trichoderma viride and New Aule Instant Dry Yeast. The purpose of this research is to measure bioetanol production from cassava peels using three different culture methods i.e SHF1 (A. niger 24 hours +New Aule Instant Dry Yeast); SHF2 (T. viride 24 hours+New Aule Instant Dry Yeast); and SSF (A. niger + T. viride + New Aule Instant Dry Yeast). The research results showed SHF1 (2,58 g/l) produced higher ethanol than that of SHF2 (2,15). The methods of SSF eficiency produced ethanol (2,93 g/l) and faster (18 hours) compared the methods of SHF1 and SHF2 which need 48 hours incubation time to reach maximum level. Keywords: bioethanol, cassava peels, SHF, SSF, A.niger, T.viride, new aule instant dry yeast